Do the Definitions of Elder Mistreatment Subtypes Matter? Findings From the PINE Study - Dong, XinQi (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND. Elder mistreatment (EM) is a pervasive public health issue and is associated with morbidity and premature mortality. This study aimed to examine how the prevalence of EM and its subtypes vary using different definitions among U.S. Chinese older adults. METHODS. The Population Study of Chinese Elderly in Chicago is a population-based epidemiological survey of 3,159 U.S. Chinese older adults in the Greater Chicago area that is guided by a community-based participatory research approach. Participants answered questions regarding psychological, physical, and sexual abuse, caregiver neglect, and financial exploitation. Definitional approaches for EM and its subtypes were constructed from least restrictive to most restrictive. RESULTS. Using different definitional criteria, the prevalence of psychological abuse was 1.1%–9.8%, physical abuse was 1.1%, sexual abuse was 0.2%, caregiver neglect was 4.6%–11.1%, and financial exploitation was 8.8%–9.3%. Overall, EM varied from 13.9% to 25.8%, depending on the defining criteria. Regardless of the definition used, those who experienced EM were more likely to be older and have higher educational attainment, poor health status, poor quality of life, and worsened health change in the last year. However, among the different definitions of overall EM, there were no statistically significant differences across sociodemographic characteristics or self-reported health status associated with EM criteria. CONCLUSIONS. Elder mistreatment is prevalent among U.S. Chinese older adults regardless of the definitional criteria. Sociodemographic characteristics associated with EM did not differ by definitional criteria. Future longitudinal studies are needed to quantify the risk and protective factors associated with EM in Chinese aging populations.